FTA Highlight No.12 – Adaptation to Climate Change with Forests, Trees and Agroforestry - Meybeck, A.; Licona Manzur, C.; Gitz, V.; Dawson, Ian K.; Martius, C.; Kindt, R.; Louman, B.; Djoudi, H.; Duguma, L.A.; Somarriba, E.; Duchelle, Amy E.; Gebrekirstos, Aster; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Forest, trees and agroforestry are crucial for adaptation to climate change in two ways that make the sector unique. First, forests and trees are already affected by climate change, and their resilience to climate impacts is a prerequisite for forest and ecosystem health and the provision of ecosystem services, including carbon sequestration. Second, forests, trees and agroforestry resources are vital to the livelihoods of forest dependent-people and the adaptation of other sectors, and to rural to urban communities overall, starting with agricultural systems and farming households, from local to continental scale, given the effects of trees and forests on local climate, the water cycle, and the provision of resources, products and ecosystem services, which are vital for many people. This highlight synthesizes the science and the engagement work done by the CGIAR Research Program on Forests, Trees and Agroforestry (FTA) on the adaptation of forests, trees and agroforestry, and on their contribution to the adaptation of people and landscapes. FTA work includes the assessment of the impacts of climate change on forests, trees, and on the people and sectors that depend on them. It also increases the understanding of the roles of forests and trees as providers of ecosystem services, how these roles might be affected by climate change, and how forests and trees contribute to building the resilience of people and landscapes. FTA initiatives also include work on tree genetic resources and how they can be made available to smallholders, and on practices for adaptation and on ecosystem-based adaptation (EbA). This highlight also describes the contribution of FTA to national policies and to global narratives on climate action, including joint mitigation and adaptation approaches and naturebased solutions.